Pulsatile lung deformation derived from maximum principal strain of cardiac cine magnetic resonance imaging: assessment of systemic sclerosis related pulmonary fibrosis - Kasuga , Noriko; Nagao , Michinobu; Ohashi , Ryoko; Sakai , Reiko; Ishizaki , Umiko; Ogawa , Yuko (Seram, 2021)
Purpose Systematic sclerosis (SSc) is characterized by the progression of fibrosis in the all organs. Pulmonary fibrosis and cardiac involvement are important prognostic factors. The present study proposes a new imaging technique to analyze pulsatile lung deformation using feature tracking of cardiac cine MRI (FT-CMR), and investigates the relation to pulmonary fibrosis and cardiac deterioration in SSc . Materials and Methods Data of cardiac MRI for 50 SSc patients with (mean age,58.04 years, Female 80%, diagnosis of interstitial pneumoniaaffection 46%) who were suspected cardiac involvement was analyzed. Cardiac cine MR imaging of short-axis left ventricle was performed using a SSFP sequence with 3.0 Tesla. Cine images in which posterior wall of the left ventricle is closest to the left lung and the mostly movement by heart beat were selected. Peripheral zone of the lower lung with a depth of 1 cm from the pleura were set as a region of interest, and the strain in the radial direction to the center of the left lung was calculated using FT-CMR. The maximum absolute value of the strain during a cardiac cycle was defined as lung strain, and was used as an estimate of pulsatile lung deformation. The presence of pulmonary fibrosis was identified by chest high-resolution CT. Comparison of lung strain was analyzed by Mann-Whitney test. Results CT showed pulmonary fibrosis in 23 SSc patients (46%). Lung strain was significantly lower for SSc patients with pulmonary fibrosis (7.2±5.5%) than those without it (11.3±11.1%; 10.5±7.4%; p50 (20%). There was no significant difference in lung strain between SSc patients with LVEF 50% (6.8±3.6% vs.9.8±9.9%). Conclusion Development of pulmonary fibrosis in SSc associates with decreasing pulsatile lung deformation regardless of cardiac deterioration. FT-CMR derived lung strain is a new functional technique for assessment of pulmonary fibrosis. 単語数301 Clinical Relevance () Cardiac cine MRI adding lung strain enables non-invasively both evaluations of cardiac function and pulmonary fibrosis.